THE IMPORTANCE OF THE EFFECTIVENESS LEADERSHIP CONCEPT IN BUILDING ISLAMIC EDUCATION - Muhammad Rifa'i (UIN Sumatera Utara Medan, 2019)
The leadership is needed by Islamic education those who have a strong soul and aware that education is required by a nation. It is not uncommon for Islamic education leaders to carry out their duties only at the level of implementation and administration of government policies. The leader of Islamic education must be someone who fully understands the Leadership Concept and has a vision for the future and has the desire to bring the organization forward and become an agent capable of answering the challenges of changing times because Islamic education institutions themselves are dynamic institutions and have an enormous responsibility for all parties, especially Religion, society, and the State. The success of the school in achieving the goal is one of the primary keys, namely the principal. In achieving the goal of an Islamic education institution that becomes the guide of the success of the headmaster, it is determined by the management's ability and leadership capacity. For the educational environment, educational leadership is a leadership that focuses on improving the quality of education. Besides the quality, leadership is also needed to increase teachers and administrator performance and school environment.